Gingipains as a virulence factor in the oral cavity - Lopes, Pedro Campos (2012)
Aim: The objective of this study is to demonstrate the molecular action of Porphyromonas gingivalis cysteine proteases such as gingipains (R1, R2 and K) upon human molecules. Materials and methods: Using the information on protein structure and function available in international databases (UniProtKB and Merops Database), the molecular interactions already described between gingipains and host molecules were clarified. Results: Possible cleavage sites were identified in host-produced elastase inhibitors and in pro-Matrix MetalloProteinase (MMP)1. Analysis of the results leads to the suggestion that the elastase inhibitor alpha1-antitrypsin is also degraded by interpain A, a cystein protease of Prevotella intermedia sharing a high homology with the PrtT and periodontain of P. gingivalis. Conclusion: The information obtained suggests a synergistic molecular mechanism by which cysteine proteases of different bacteria can be responsible for the clinical manifestations of periodontal disease, and illustrates the use of bioinformatics to establish and predict molecular mechanisms.